Results of a differential approach to surgical treatment of proximal humerus fractures in patients with osteoporosis - Korzh, Mykola; Makarov, Vasyl; Gupalov, Igor; Pertseva, Olena; Boyko, Konstantin; Pidgaiska, Olga (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Objective. To conduct a comparative retrospective analysis of the anatomical and functional results of surgical treatment of proximal humerus fractures AO/OTA 11-B, 11-C using different methods in patients over 50 years old with osteoporosis to justify a differential approach. Methods. The study included 102 patients aged 50 years and older with osteoporosis and proximal humerus fractures AO/OTA 11-B, 11-C. The patients were divided into three groups: I — 50 (16 men, 34 women) whom were performed open reduction and internal fixation (ORIF) with the PHILOS plate; II — 44 (8 men, 36 women) — ORIF with the PHILOS plate and using 3D polylactide (PLA) porous implants were applied; III — 8 (2 men, 6 women) whom were performed primary reversed total shoulder arthroplasty (RTSA) with developed total reversible endoprosthesis. The results of treatment were evaluated according to the Constant-Murley Shoulder Score system after 3, 6, 12 months. The results. Positive results in the first group were obtained in 72.0 % of patients (the average Constant-Murley Shoulder Score after 12 months was 78.4 points); in the second — in 81.8 % (88.0 points); in the third — 75.0 % (82.0 points). A differentiated approach to the choice of surgical treatment of patients aged 50 years and older with fractures AO/OTA 11-B, 11-C is proposed. The clinical trial of the reverse total modular shoulder endoprosthesis developed by us using porous 3D titanium parts, manufactured by additive technologies, showed positive short-term results. The design features of the device increase the reliability and durability of proposed endoprosthesis. Conclusions. RTSA in the case of unstable proximal humerus fracture or in the case of metal structure migration after primary ORIF in patients with low bone mineral density is the effective surgical intervention that allows to achieve satisfactory functional results in up to 3 years.